Physical health in young males and risk of chronic musculoskeletal, cardiovascular, and respiratory diseases by middle age: A population-based cohort study. - Aleksandra Turkiewicz; Karin Magnusson; Simon Timpka; Ali Kiadaliri; Andrea Dell'Isola; Martin Englund (PLoS Medicine)
Background Cardiovascular, respiratory, and musculoskeletal disease are among the leading causes of disability in middle-aged and older people. Health and lifestyle factors in youth have known associations with cardiovascular or respiratory disease in adulthood, but largely unknown associations with musculoskeletal disease. Methods and findings We included approximately 40,000 18-year-old Swedish males, who completed their conscription examination in 1969 to 1970, followed up until age of 60 years. Exposures of interest were physical health: body mass and height, blood pressure, pulse at rest, muscle strength, cardiorespiratory fitness, and hematocrit; self-reported lifestyle: smoking, alcohol, and drug use; self-reported health: overall, headache and gastrointestinal. We followed the participants through the Swedish National Patient Register for incidence of common musculoskeletal (osteoarthritis, back pain, shoulder lesions, joint pain, myalgia), cardiovascular (ischemic heart disease, atrial fibrillation), and respiratory diseases (asthma, chronic obstructive pulmonary disease, bronchitis). We analyzed the associations using general estimating equations Poisson regression with all exposures included in one model and adjusted for parental education and occupation. We found that higher body mass was associated with higher risk of musculoskeletal (risk ratio [RR] per 1 standard deviation [SD] 1.12 [95% confidence interval, CI 1.09, 1.16]), cardiovascular (RR 1.22 [95% CI 1.17, 1.27] per 1 SD) and respiratory diseases (RR 1.14 [95% CI 1.05, 1.23] per 1 SD). Notably, higher muscle strength and cardiorespiratory fitness were associated with higher risk of musculoskeletal disease (RRs 1.08 [95% CI 1.05, 1.11] and 1.06 [95% CI 1.01, 1.12] per 1 SD difference in exposure), while higher cardiorespiratory fitness was protective against both cardiovascular and respiratory diseases (RRs 0.91 [95% CI 0.85, 0.98] and 0.85 [95% CI 0.73, 0.97] per 1 SD exposure, respectively). We confirmed the adverse effects of smoking, with risk ratios when comparing 11+ cigarettes per day to non-smoking of 1.14 (95% CI 1.06, 1.22) for musculoskeletal, 1.58 (95% CI 1.44, 1.74) for cardiovascular, and 1.93 (95% CI 1.60, 2.32) for respiratory diseases. Self-reported headache (category "often" compared to "never") was associated with musculoskeletal diseases (RR 1.38 [95% CI 1.21, 1.58]) and cardiovascular diseases (RR 1.29 [95% CI 1.07, 1.56]), but had an inconclusive association with respiratory diseases (RR 1.13 [95% CI 0.79, 1.60]). No large consistent associations were found for other exposures. The most notable associations with specific musculoskeletal conditions were for cardiorespiratory fitness and osteoarthritis (RR 1.23 [95% CI 1.15, 1.32] per 1 SD) and for muscle strength and back pain (RR 1.18 [95% CI 1.12, 1.24] per 1 SD) or shoulder diseases (RR 1.27 [95% CI 1.19, 1.36] per 1 SD). The main limitations include lack of adjustment for genetic factors and environmental exposures from childhood, and that the register data were available for males only. Conclusions While high body mass was a risk factor for all 3 studied groups of diseases, high cardiorespiratory fitness and high muscle strength in youth were associated with increased risk of musculoskeletal disease in middle age. We speculate that these associations are mediated by chronic overload or acute trauma.